SAS procedures guide. - SAS Institute,.; SAS Institute (Cary, N.C. : SAS Institute, 1990)
This guide provides complete reference information for all procedures in Release 6.06 base SAS software. It is written for users who have not used the SAS System but who have some computer programming experience and know the fundamentals of programming logic. It is also written for experienced SAS users.
Includes index.
Includes bibliographical references.
Keywords: SAS Institute; SAS (Computer program); SAS (Logiciel); Statistics -- Data processing; SAS; SAS (Syst(3d(Beme informatique).s